2010
DOI: 10.1590/s1806-66902010000200002
|View full text |Cite
|
Sign up to set email alerts
|

Microbial soil quality indicators under different crop rotations and tillage management

Abstract: -An experiment was carried out under field conditions to assess the effects of soil management (no-tillage-NT and conventional tillage-CT) and crop rotation systems on microbial biomass-C (C mic ), basal soil respiration (BSR), metabolic quotient (qCO 2 ), soil organic carbon content (C org ) and microbial carbon to organic carbon ratio (C mic /C org ). Soil samples were collected on an area cultivated with wheat as winter crop and soybean as summer crop, both in rotation with vetch, maize and oats. Samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
20

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
0
11
1
20
Order By: Relevance
“…The study of associations between biological and chemical attributes is important for understanding the best management practices in order to improve soil quality. Moreover, soil macrofauna can act as an indicator of environment-soil changes (Lavelle, 1997), and microbial properties allied to total organic carbon content can be used to assess the sustainability of agricultural production (Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The study of associations between biological and chemical attributes is important for understanding the best management practices in order to improve soil quality. Moreover, soil macrofauna can act as an indicator of environment-soil changes (Lavelle, 1997), and microbial properties allied to total organic carbon content can be used to assess the sustainability of agricultural production (Ferreira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There was high variability in the results for the variable MBC regarding the evaluated factors. Several studies have found differences in the content of MBC due to the plant cycle, adding crop residues, tillage systems, and crop rotation (Franchini et al, 2007;Ferreira et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Soil microbial communities are influenced by many factors, including cover crops and soil management (Ferreira et al, 2010), development stage of plants and cultivars (Ferreira et al, 2008), fertilizer type (Carrera et al, 2007), and pesticide application (Ferreira et al, 2009). Studies about the interactions between plants and soil microorganisms are important to understand a variety of processes, such as nutrient cycling, ecosystem functioning, and C sequestration (Singh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tubos contendo concentrações crescentes de carbono em mg mL -1 em solução de biftalato de potássio após a digestão, utilizadas para a construção da curva padrão em cada comprimento de onda. de onda a diferença numérica em favor do solo de mata, como esperado, corroborando Ferreira et al (2010). O C mic obtido por titrimetria, no Latossolo Vermelho proveniente da área de mata, apresentou-se significativamente maior em relação àqueles obtidos por espectrofotometria, nas duas profundidades.…”
Section: Resultsunclassified